The Sin of Laura: The Meaning of Culture in the Education of Nineteenth-Century Women - Theobald, Marjorie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
Abstract In the iconography of nineteenth-century female education, the centralfigure is a woman at the piano. This figure embodies a form ofeducation, the female "accomplishments" — music, art, modern languages, literature, and the natural sciences — which was widespread in Britain by the end of the eighteenth century and which spread rapidly throughout the English-speaking world. Yet this form of education has been overlooked or dismissed by both mainstream and feminist historiography. This paper considers the rise of the accomplishments curriculum as a precursor to the emergence, late in the nineteenth century, of the “worthwhile education” of women. This earlier development, in the author's view, requires a reconsideration of that sacred cow of feminist theory, the man/culture, women/nature dichotomy. A study of the female accomplishments also illustrates the earlier rise of the enduring and oppressive myth that there is a natural affinity between the humanities and the female mind — with its equally enduring implication that there is a natural affinity between science and the male mind. Historians of the Edwardian period have noted that the rational, scientific frame of mind, which underpinned the capitalist exploitation of the natural world, was considered to be a "natural" male predilection. Feminist historians have rightly exposed the use of this pseudo-science as a justification of the contemporary intellectual subjugation of women. They have, however, failed to note that intellectual attitudes which were evident more than a century earlier, and which underpinned the emergence of the female accomplishments, ensured that women would be excluded from the great intellectual adventure of the twentieth century.